New benefit sharing rules for digital sequence information under the Convention on Biological Diversity and the Plant Treaty: ensuring mutual supportiveness - Halewood, Michael; Masso, Cargele; López Noriega, Isabel (CGIAR, 2024)
EHB platform webinar #4. No fewer than four UN fora – UNEP, FAO, WHO and the General Assembly– are currently hosting negotiations of new rules to increase benefit sharing from the use of digital sequence information (DSI). Of course, increasing the equitable redistribution of monetary and nonmonetary benefit is critically important. But there is a risk that if these new rules are not well coordinated, and if the boundaries between them are not clear, they will create confusion and insuperable transaction costs for stakeholders involved in the conservation and sustainable use of biological diversity.